A review on synthesis of mullite ceramics from industrial wastes - Choo, Thye Foo; Mohd Salleh, Mohamad Amran; Kok, Kuan Ying; Matori, Khamirul Amin (MDPI, 2019)
Some industrial wastes are shown to be useful in the production of mullite ceramics. These industrial wastes are rich in certain metal oxides such as silica (SiO2) and alumina (Al2O3). This gives wastes the potential to be used as a starting material source for mullite ceramics preparation. The purpose of this review paper is to compile and review various mullite ceramics preparation methods that utilized a variety of industrial wastes as starting materials. This review also describes the sintering temperatures and chemical additives used in the preparation and its effects. A comparison of both mechanical strength and thermal expansion of the reported mullite ceramics prepared from various industrial wastes were also addressed in this work.